Coordinatively stiffen and toughen polymeric gels via the synergy of crystal-domain cross-linking and chelation cross-linking - Jipeng Zhang; Miaoqian Zhang; Huixiong Wan; Jinping Zhou; Ang Lu (Nature Communications)
Abstract Polymer gels have been widely used in flexible electronics, soft machines and impact protection materials. Conventional gels usually suffer from the inherent conflict between stiffness and toughness, severely hampering their applications. This work proposes a facile yet versatile strategy to break through this trade-off via the synergistic effect of crystal-domain cross-linking and chelation cross-linking, without the need for specific structure design or adding other reinforcements. Both effects are proven to boost the mechanical performance of the originally weak gel, and result in a stiff and tough conductive gel, achieving significant enhancements in elastic modulus and toughness by up to 366-, and 104-folds, respectively. The resultant gel achieves coordinatively enhanced stiffness (110.26 MPa) and toughness (219.93 MJ m−3), reconciling the challenging trade-off between them. In addition, the presented strategy is found generalizable to a variety of metal ions and polymers, offering a promising way to expand the applicability of gels.